2013
DOI: 10.3109/00016357.2013.788734
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment in young adults: A 3-year validation of clinical guidelines used in Public Dental Service

Abstract: The risk assessment scheme used by the Public Dental Service for young adults relied basically on past and current caries activity and 65-70% of the patients were correctly classified. The model was most effective to screen out patients with low caries risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The rational to select a cumulative preventive score 0–3 as ‘basic prevention’ was based on the assumption that this preventive care basically was delivered in association with the regular check‐ups while a score 4–9 (‘additional prevention’) indicated that the patient was recalled and treated at least once between the regular intervals during the study period. It should also be stressed that the baseline risk grouping was based on the patient's caries situation in 93.2% of all cases which explained the present focus on the anticaries activities implemented by the clinicians.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The rational to select a cumulative preventive score 0–3 as ‘basic prevention’ was based on the assumption that this preventive care basically was delivered in association with the regular check‐ups while a score 4–9 (‘additional prevention’) indicated that the patient was recalled and treated at least once between the regular intervals during the study period. It should also be stressed that the baseline risk grouping was based on the patient's caries situation in 93.2% of all cases which explained the present focus on the anticaries activities implemented by the clinicians.…”
Section: Discussionsupporting
confidence: 71%
“…The selection of the material and the socio-economic characteristics has been further detailed in a previous publication (8). The attrition rate was 24.2% over 3 years, mostly due to relocation, leaving 982 patients for the final analyses (for a flow chart, see (9). All the participants were residents in areas with low natural fluoride content in the drinking water supply but they reported use of fluoridated dentifrice on regular basis.…”
Section: Study Groupmentioning
confidence: 99%
“…The selection and enrolment of the study cohort has been described before [6]. In brief, 1699 19-year-olds were invited from eight different Public Dental Clinics (PDC’s) across the region to form a representative sample of this age group.…”
Section: Methodsmentioning
confidence: 99%
“…At baseline, the risk category of each patient was assessed by the patient’s regular dental team (dentist and/or dental hygienist) according to the “adult guidelines for risk assessment of oral diseases” issued by the regional Public Dental Service. Based on clinical and radiographic findings, the risk grouping relied on past and present caries, periodontal conditions, general risk and technical risk as previously described [6]. Four risk categories were used and each patient was classified into one of the following risk groups; “low risk” (42.7%), “some risk” (45.4%), “high risk” (10.4%) and “very high risk” (1.5%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation